Comparative analysis of stormwater management in Finland and Latvia - Hladii, Viktoriia (My University, 2019)
Stormwater management has entered environmental and political discourse especially with realisation and initiation of climate change adaptation measures, predominantly as the major contributor to the pollution of receiving waters. Defined as “excessive surface runoff that is generated on impermeable surfaces during precipitation events and snow/ice melt”, the question of stormwater management is touching upon two contemporary problematic trends – adverse effects of climate change (e.g. raising level of precipitation) and increasing urbanisation and densification of the residential areas. The purpose of this master’s thesis is to define the notion of stormwater as it is seen by the legislation and policy documents of Finland and Latvia, to examine and compare structures of stormwater administration in the two states, and to investigate how stormwater administration is fragmented within the vertical and horizontal dimensions of environmental administration, taking into consideration highly cross-sectoral nature of stormwater management. The result of my research is a comprehensive description and comparison of two case studies, where current state of stormwater administration is presented given the certain level of administrative fragmentation and mechanisms of stormwater management described. The thesis gives an overview of two different systems where relatively similar policies (transposed from the EU) are implemented in different ways and different circumstances.
Keywords: Stormwater administration, environmental administration, stormwater management, fragmentation, decentralisation, water management, comparative study, Baltic Sea region, Finland, Latvia